The effect of adolescent empowerment on changes in knowledge and attitudes about pramarital sexual behavior - Arisjulyanto, Dedy; Ika Puspitas, Nanik; Hendry, Zul; Alwi Andi, Muhammad (BKM Public Health and Community Medicine, 2021)
Purpose: Youth is the future generation of the nation. However, currently, a lot is happening to adolescents, such as premarital sexual behavior which ultimately has an impact on early marriage and the spread of sexually transmitted diseases. Many factors influence both internal and external factors causing juvenile delinquency that need attention. To overcome this, a good environment can be decisive for the development of these adolescents. And currently, the number of Indonesian adolescents aged 10-24 years in 2017 was 67.36 million or around 25% of Indonesia's population, the rate of early marriage in NTB is above the national figure, namely 31.12%. And the case of early marriage in NTB is very high, namely 58.1% of the total marriages in NTB. Method: This study used a "Pre Experimental Design". The population in this study were adolescents in the Karang Luah neighborhood, Bertais Village, Mataram City, and the samples in this study were 32 people who were taken using the total sampling technique. Result: The results of this study indicate the difference in the average value of the knowledge level of adolescents before and after the empowerment of adolescents, the p-value = 0.000 < α = 0.05. And experiencing changes in attitudes towards premarital sexual behavior for the better after being given empowerment of adolescents with a p-value = 0.000< α = 0.05. Conclusion: This research can conclude that there are differences in the value of the level of knowledge and attitudes of adolescents about sexual behavior after being empowered by adolescents in Karang Luah, Bertais Village.